Akibat Hukum Pembatalan Secara Sepihak Oleh Konsumen Dalam Perjanjian Pemasanan Ojek Online Gaskeun Delivery - Heris Suhendar; Qotrunada, Anissa; M. Ilham T , M. Ilham T (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Unilateral cancellation of orders by consumers intentionally on the online motorcycle taxi service gaskeun delivery can cause losses to one party and is not in accordance with the principles of the agreement. This study discusses unilateral cancellation by consumers and its legal consequences on the online motorcycle taxi service gaskeun delivery. Further discusses dispute resolution. The research method uses empirical legal research with a qualitative approach, laws and conceptual regulations. The results of the study indicate that unilateral cancellation of an agreement without any reason justified by law is an unlawful act. The legal consequences of unilateral cancellation of an agreement are the emergence of the right to claim compensation for the party who canceled and the obligation to compensate for the party who canceled the agreement. The approaches that can be used in resolving unilateral cancellation of an agreement are the interest-based and right-based approaches. The interest-based approach is the first choice, because this approach can be carried out effectively and efficiently, considering the amount of loss caused by the act is not too large. This study contributes to the development of contract law, especially the settlement of cancellation of agreements.